Upaya Meningkatkan Hasil Belajar PKn Tentang Nilai- Nilai Juang dalam Proses Perumusan Pancasila sebagai Dasar Negara pada Peserta Didik Kelas VI A SD Negeri Kasreman melalui Metode Tari Bambu di Semester I Tahun Pelajaran 2018/2019 - Rokhimah Rokhimah (Universitas Sebelas Maret, 2019)
The type of this research is a Class Action Research (CAR) with thepurpose to analyze the application of the civic education’s learning outcome aboutthe fighting values in Pancasila formulation as the state foundation of the studentsof Class VI A the Elementary School of Kasreman with the bamboo dancingmethod on the first Semester of the 2018/2019 year academic. The subjects of thisresearch are the students of Class VI A the Elementary School of Kasreman on thefirst Semester of the 2018/2019 year academic as much as twenty one children;consist of fourteen boys and seven girls. The data resources of this research arerelating with learning activities and learning outcomes. Techniques of collectingdata of this research are using non test technique and test technique. Technique ofanalyzing data of this research is using comparative description. The procedure ofthis research is an action research with the spiral model. The results of this researchare 1) the Civic Education’s learning about the fighting values in Pancasilaformulation as the state foundation is an individual and different task for eachstudent, 2) the Civic Education’s learning about the fighting values in Pancasilaformulation as the state foundation is only a single task with an optional question,3) the Civic Education’s learnings about the fighting values in Pancasilaformulation as the state foundation are increasing the learning activities; activelyanswering the questions form the teacher and other students, very actively askingthe questions to the teacher and actively declaring the opinions and 4) the CivicEducation’s learnings about the fighting values in Pancasila formulation as thestate foundation are increasing the learning outcomes. The learning outcomes onthe Early Condition are 62,14 for the average and 42,85% for the completeness.The learning outcomes on the First Cycle are 72,14 for the average and 71,42% forthe completeness. The learning outcomes on the Second Cycle are 82,85 for theaverage and 85,71% for the completeness.